Peculiarities of endurance development for first year students - A.G. Pochernina; M.G. Pochernina; E.V. Selivanov (Pedagogics, Psychology, Medical-Biological Problems of Physical Training and Sports, 2014)
Purpose: to determine the dynamics of the specific endurance first-year students in the classroom of physical education. Material : the study involved 20 students. Conducted educational testing: seed of lifting in supine position, hang on bent arms, jumping from sitting up with the stop, run 30m, bending and straightening the arms in emphasis lying, tilt forward from a sitting position, shuttle run, broad jump start. Results : found that the passage of the training module volleyball observed development of specific endurance and all motor abilities. Established that the manifestation and development of motor skills are interrelated. Since force is a functional foundation for the development of other skills, flexibility - the foundation of all mechanical movements. Without the development of strength, speed, coordination abilities impossible to develop endurance. Therefore, it is inappropriate and incorrect receipt of unidirectional only specific endurance (dynamic power and static, speed-power). Conclusions: indicated the need to achieve functional specialization of the body in the direction which is necessary for high-level manifestation of certain motor skills.